Acute myocardial infarction treated with novel Resolute Onyx and Orsiro stents in the randomized BIONYX trial. Issue 2 (10th March 2021) - Ploumen, Eline H.; Buiten, Rosaly A.; Zocca, Paolo; Doggen, Carine J. M.; Jessurun, Gillian A. J.; Schotborgh, Carl E.; Roguin, Ariel; Danse, Peter W.; Benit, Edouard; Aminian, Adel; Anthonio, Rutger L.; Somi, Samer; et al.
Abstract: Objectives: To compare 2‐year outcome following treatment with drug‐eluting stents (DES) for acute myocardial infarction (MI) versus non‐MI clinical syndromes. In acute MI patients, a stent‐level comparison was performed, comparing Resolute Onyx versus Orsiro stents. Background: In patients presenting with acute MI, higher adverse event rates have been reported. So far, no clinical results >1 year have been published of acute MI patients treated with Resolute Onyx. Methods: This post‐hoc analysis of the randomized BIONYX trial( NCT02508714 ) assessed the main outcome target vessel failure (TVF: cardiac death, target vessel MI, or target vessel revascularization) with Kaplan–Meier methods. Results: Of all 2, 488 trial participants, acute MI patients ( n  = 1, 275[51.2%]) were significantly younger and had less comorbidities than non‐MI patients ( n  = 1, 213[48.8%]). TVF rates were lower in acute MI patients (77/1, 275[6.1%] vs. 103/1, 213[8.6%], HR:0.70, 95%‐CI 0.52–0.94; plog‐rank  = 0.02), mainly driven by target vessel revascularization (4.1 vs. 6.1%, plog‐rank  = 0.03). Multivariate analysis showed no independent association of clinical syndrome with TVF (adjusted‐HR: 0.81, 95%‐CI 0.60–1.10; p  = .17). In MI patients treated with Resolute Onyx ( n  = 626) versus Orsiro ( n  = 649), there was no difference in TVF (6.2 vs. 6.1%; plog‐rank  = 0.97) and its components. There was only 1(0.2%) definite‐or‐probable stent thrombosis in RO‐ZES and 8(1.2%) in O‐SES ( p  = .053). Conclusions: Two years after treatment with thin‐strut DES in this randomized trial, patients treated for acute MI had lower adverse event rates than non‐MI patients. Yet, these findings were mainly attributable to between‐group differences in patient and lesion characteristics. In patients who underwent PCI for acute MI, both Resolute Onyx and Orsiro showed favorable and similar 2‐year outcomes.